Belastningshistoria: Den vindlande vägen mot en hållbar fotgängarlogistik (Toulouse 1900–2011) - Cochoy, Franck; Canu, Roland; Calvignac, Cédric (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
This article is about an ignored part of the history of mobility: the practice of displaying goods by foot. It departs from an archive with photos of pedestrians in Toulouse, France from the past 100 years, out of which we have selected 600 from four different periods. We have used a method combining archaeology, ethnography and statistics. All the photos have been systematically observed and coded. This way we have been able to detect some striking changes of carrying techniques and equipment. Overall more and more people of all social classes carry more and more objects but still manage to keep their hands free. This is due to an huge increase of the amount of shoulder bags and backpacks. In 2011 more than 60 percent of all loads were carried this way in Toulouse as opposed to only eight percent before WW2. But not only has the development of new techniques and equipment mattered. Walking style and carrying is also dependent on fashion an increasing leveling of social inequalities. At the turn of the 19 th century it was high fashion among men to walk with their hands behind. This was not only high fashion among bourgeoisie men, but also made possible by the help of servants doing the shopping for their masters, and relieving the latter of the necessity to carry heavy burdens.